An evaluation method for green logistics system design of agricultural products : a case study in Shandong province, China - Ni, Songyuan (2019)
Recently, the environmental issue caused by logistics of agricultural products has attracted a great deal of attention. In order to solve the problem, much of work focuses on green logistics to decrease environmental pollution. However, the green logistics evaluation system of agricultural products is insufficient. Therefore, establishing a reasonable green logistics evaluation system for agricultural products plays a key role in the development of green agricultural products. In this work, domestic and international environmental factors which affect the development of the green logistics of agricultural products are analyzed based on reduction, reuse, and recycling principle of circular economy. In addition, a series of evaluation indicators for green logistics of agricultural products are developed. A fuzzy analytic hierarchy process method is proposed to make a comprehensive evaluation for green logistics of agricultural products based on evaluation indicators. The method combined analytic hierarchy process and fuzzy theory, where a fuzzy transformation operator is introduced. The proposed method is applied for decision-maker in view of knowledge management. In order to verify the applicability of approach, the approach is applied to green logistics of Shandong agricultural products.